Upaya Peningkatan Aktivitas Belajar Mahasiswa Melalui Lesson Study Matakuliah Dasar Teknik Digital - Ilmiyati Rahmy Jasril (invotek, 2019)
This study aims to describe the learning activities of students in Digital Engineering Basic Subjects through lesson study. This research is an action research study. The research method follows the Plan, Do and See stages in the lesson study which is conducted in two cycles. The reflection made by the model lecturer in collaboration with the observer as a reference for learning improvement. The implementation of lesson studies can have a positive impact on student activities in the learning process including thinking together, asking questions, answering, collaborating, actively discussing, making decisions, applying and analyzing equations and circuits in learning Digital Techniques. Keywords : Lesson Study, Student Activities and Basic Digital Engineering